Pulmonary Artery Versus Aortic Root Venting and Early Postoperative Respiratory Recovery After On-Pump Coronary Artery Bypass Grafting: A Propensity Score Overlap-Weighted Analysis - Seval Kılbasanlı; Esra Ertürk Tekin (Journal of Clinical Medicine, 2026)
Background/Objectives: Direct comparative evidence regarding aortic root and pulmonary artery venting during on-pump coronary artery bypass grafting (CABG) remains limited. We evaluated whether pulmonary artery venting was associated with improved early postoperative respiratory recovery compared with aortic root venting. Methods: This single-center retrospective cohort included 488 adults undergoing on-pump CABG between January 2020 and January 2025 (aortic root vent, n = 316; pulmonary artery vent, n = 172). The primary outcome was delayed extubation beyond 8 h. Propensity-score overlap weighting based on 22 covariates addressed baseline confounding. Confidence intervals and p values were obtained from 5000 stratified nonparametric bootstrap samples with refitting of the propensity-score model and recalculation of overlap weights in each sample. Results: Extubation-time data were available for 486 patients. As expected with overlap weighting based on a logistic propensity-score model, exact mean balance was achieved for the covariates included in the model (absolute standardized mean differences < 0.001). The overlap-weighted risk of delayed extubation was 51.4% in the aortic root vent group and 41.1% in the pulmonary artery vent group; the adjusted association was not statistically significant (odds ratio [OR] 0.66, 95% confidence interval [CI] 0.37–1.10; p = 0.110). Pulmonary artery venting was associated with lower odds of fast-track failure (OR 0.53, 95% CI 0.30–0.89), the respiratory composite outcome (OR 0.35, 95% CI 0.17–0.64), and postoperative inotrope requirement (OR 0.39, 95% CI 0.14–0.87), together with a higher arterial oxygen partial pressure (PaO2) at extubation (mean difference 7.08 mmHg, 95% CI 0.72–12.89). Conclusions: The primary outcome of delayed extubation did not differ significantly between venting strategies after overlap weighting. Favorable associations across several secondary outcomes suggest a possible improvement in broader early postoperative recovery with pulmonary artery venting; these exploratory findings require prospective confirmation.